Investigating the causes of the downfall of democracy in Afghanistan from 2001 up to 2021 - Khurami, Hafiza; Safi, Shafiqa Royesh; Payman, Mariam (Technium Business and Management, 2023)
Democracy in a country always fall due to internal and external factors. The collapse of Democracy not only brings political instability in a country, but it can negative impacts of the countries that have Democracy system. In developing countries, external and internal problems cause Democracy to fall. Afghanistan's geopolitics place is very important for superpowers, these powers have tried to control political power in Afghanistan directly and indirectly. For this reason, this country has always been dependent on the superpowers of the world, such as England in the 18th and 19th centuries, the Soviet Union in the 20th century, and America in the 21st century, it has been the external factors that caused political instability in Afghanistan, internal factors such as ethnic and language discrimination, economic dependence, weaken the political system causes Democracy to fall in Afghanistan.